Thống kê Bayes và ứng dụng trong dự báo giá chứng khoán của các ngân hàng và công ty tài chính ở Việt Nam - Nguyễn Phát, Đạt; Lê Thanh, Hoa; Phạm Thế, Bảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
Forecasting has gained much attention in recent years, especially in economics and finance sectors. Once the forecast is good enough, the result will be helpful for enterprises in making decisions as well as for investors in maximizing profit. According to Decision No. 242/QĐ-TTg dated February 28th, 2019 of the Vietnamese Prime Miniter approves the project "Restructuring the securities market and insurance market to 2020 and orientation to 2025", it requires companies to standardize their business operations, report accurately and transparently according to international standards. Thanks to transparent and accurate information, investors have sufficient information for making the most significant capital investment decisions. The Bayesian statistics combine past information and prior knowledge for making accurate forecasts. Short-term forecasting problems usually use the information at time ???? to predict the one at ???? + 1. However, for the Vietnamese stock market, investors need a prediction at ???? + 3, when it is possible for trading recently purchased stocks. Under these circumstances, investors could minimize potential risks.
Keywords: Bayesian statistics; Stock price forecasts; Bank securities code; Financial companies